29.4k views
0 votes
What is the missing term? (10x – 4x2) – (7x + ?) = 3x – 6x2

User Dube
by
6.0k points

2 Answers

4 votes
10x-4x^2-7x-a=3x-6x^2
3x-4x^2-a=3x-6x^2
a=6x^2-4x^2
a=2x^2
User Max Martynov
by
5.4k points
4 votes

Answer:

Let the missing number be a.

Given that:


(10x-4x^2)-(7x+a) = 3x-6x^2

Remove the parenthesis we have;


10x-4x^2-7x-a= 3x-6x^2

Combine like terms we have;


3x-4x^2-a= 3x-6x^2

Subtract 3x from both sides we have;


-4x^2-a=-6x^2

Add
4x^2 to both sides we have;


-a=-6x^2+4x^2

Simplify:


-a=-2x^2

Divide both sides by -1 we have;


a=2x^2

Therefore, the missing term is,
2x^2

User Tomka
by
5.8k points